INTELLECTUAL DISABILITY AND DEAFBLINDNESS: INCLUSIVE PRACTICES OF THE TEACHER INSTRUCTOR/SPECIALIST A PROPOSAL FOR INTERVENTION BASED ON VERSIONS OF THE TALE “LITTLE RED RIDING HOOD” - Fernanda de Oliveira, Andrea; Matos Alauk, Débora; Rodrigues dos Santos, Erica (Revista Gênero e Interdisciplinaridade, 2025)
This work is part of the research line on Special Education with an emphasis on intellectual disability. It aims to develop an intervention proposal and analyze the methodologies and strategies of the instructor and specialist teacher, so they are capable of teaching deafblind students with intellectual disabilities. The focus is on literacy in written Portuguese, tactile Libras as the mother tongue, and manual or tactile Braille, based on versions of Little Red Riding Hood. To this end, our research question is: What is the importance of the instructor/specialist teacher in the academic development of deafblind students with intellectual disabilities? Based on this question, we established the following objectives: A) to understand the importance of the role of the instructor/specialist teacher in student development; B) to include deafblind students with intellectual disabilities in the educational system through appropriate pedagogical practices; and C) to assist in the teaching and learning process through an inclusive intervention proposal. The methodology used was quantitative, through an interview conducted with an instructor and specialist teacher working in a municipal public school (EMEB) with two students with multiple disabilities. This research is justified by the need to expand studies in the field of Inclusive Education focusing on intellectual disability and deafblindness through adequate pedagogical practices. Therefore, this proposal is grounded in the theoretical framework of studies on intellectual disability and deafblindness based on the following authors: concepts and practical approaches to working with students with intellectual disabilities by ROSA (2017), GRILLO (2007), MANTOAN (2003), and OLIVEIRA (2018); and the definition, levels, forms of communication and education of deafblind individuals by CAMBRUZZI & COSTA (2016), VILELA (2020), and MCINNES (1999).